Work-life management e dialogo sociale : dagli accordi di clima alla bilateralità = Work-life management and social dialogue : from corporate climate agreements to bilaterality - Iodice, Domenico (Roma, 2018)
"Work Life Management (WLM) represents a cornerstone or stone of stumbling for work organisation and industrial relations. To date, WLM and welfare constitute a management (and motivational) leverage, more than the way for companies to implement the obligation to adapt work to man in the choice of methods of work and production (Article 6, Directive 89/391 EC). It is undoubtedly difficult to make payable within the companies those rights of the person that should never be compressed by the times and ways of work. The European and National labor laws, do not keep pace with the digital evolution and related organizational processes, but in the meantime there are practices, rapid, deep transformations of the employment relationship whose overall meaning escapes. Privacy, right to disconnect, limits to employer control, right to personal communication spaces and even right to dissent/to constructive criticism are inseparable topics. They are central to the debate on WLM, yet the heteronomous legislation does not take it directly and organically. On the contrary, legislation implicitly legitimizes the unilateral regulation by employers and, in some cases (as for smart working, in Italy) explicitly refers to individual bargaining even the dedefinition of the contents of the work performance. “Natura abhorret a vacuo”: it is therefore necessary that collective bargaining immediately preside over these unexplored spaces, defining advanced individual protections and acquiring spaces of bilaterality, for a shared management of organizational processes."